Violations of the financial employee in his legal work - Waleed, Ali; Salah, Ban (Journal of Legal Sciences, 2022)
The financial violation must be defined as a concept for the purpose of distinguishing this concept from other terms that may be suspected in the context of the job and the violations of the financial employee that may be disciplinary or even punitive. From Egypt and Iraq, in addition to addressing the doctrinal aspect in the two countries above and the extent to which the specialized jurists dealt with the statement of financial violations, or even highlighting images that could be considered that the violation committed by the financial employee falls under the framework of the financial violation. Which may result in a financial violation by the financial employee, and we touched upon the request of him to indicate the financial violations in the aspect of the administrative work that the administration comes and in which there is a picture of the financial violations. A legal effect, whether by establishing a legal center, canceling it, or even modifying the legal position, and because our research is limited to the framework of the statement of financial violations committed by the authorities. The financial officer in the field of the job, we have touched upon in explaining the violations within the scope of issuing an order to spend by the financial officer with the authority, who may be, for example (the minister or the general manager) going through the actual exchange process implemented by the (accountant) for example, but the last requirement In it, we discussed the financial violations committed by the financial employee in the field of government contracts in terms of the means of contracting and implementation.